Influence Economic Growth, Inflation and Decentralization Fiscal To inequality Regional Income - Safina, Lailan (Journal of International Conference Proceedings, 2023)
This study aims to find out Influencer of Economic Growth, Inflation and Decentralization Fiscal To inequality Regional Income. This research uses approach explanatory research. The population in this study were 33 districts /cities in Sumatra north. Retrieval technique sample used  is purposive sampling method with the selected sample as many as 10 City Regencies. Data analysis used is Partial Least Square analysis. Research results obtained that Economic Growth effect to inequality Regional Income. Based on results study obtained that Inflation has no effect against inequality income area. Based on results study obtained that Decentralization Fiscal influential against